Synthetic biodegradable polymer materials in the repair of tumor-associated bone defects - Yu, Honghao; Liu, Haifeng; Shen, Yuan; Ao, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
The repair and reconstruction of bone defects and the inhibition of local tumor recurrence are two common problems in bone surgery. The rapid development of biomedicine, clinical medicine, and material science has promoted the research and development of synthetic degradable polymer anti-tumor bone repair materials. Compared with natural polymer materials, synthetic polymer materials have machinable mechanical properties, highly controllable degradation properties, and uniform structure, which has attracted more attention from researchers. In addition, adopting new technologies is an effective strategy for developing new bone repair materials. The application of nanotechnology, 3D printing technology, and genetic engineering technology is beneficial to modify the performance of materials. Photothermal therapy, magnetothermal therapy, and anti-tumor drug delivery may provide new directions for the research and development of anti-tumor bone repair materials. This review focuses on recent advances in synthetic biodegradable polymer bone repair materials and their antitumor properties.